КОММУНИКАТИВ ҚӘБИЛЕТТИ РАЎАЖЛАНДЫРЫЎШЫ СӨЗСИЗ БАЙЛАНЫС ҚУРАЛЛАРЫ - Шерниязова, Ж.Е. (FAN va JAMIYAT, 2023)
The given article focuses on introducing the means of nonverbal communication. Generally, the article is the brief description of fundamental part of investigation devoted to investigate the role of nonverbal means of communication in teaching foreign languages. The aim of the author is to describe some key types of nonverbal means of communication with the help of general facts.